Sedekah Melalui Perspektif Teologi Kontekstual Joseph Harrod Dalam Merespons Kesenjangan Sosial Ekonomi - Christian Kurniawan; Junius Najoan (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
The global economic crisis has created a gap between the rich and the poor (socio-economic gap). The decline in the spirituality of religious people is proven by their reluctance to give alms and their neglect of the importance of the essence of alms. In fact, the practice of giving alms is a pragmatic act to realize the law of love for others that has been taught in Christianity. To address this social and spiritual issue, Joseph Harrod offers a new understanding of almsgiving. This article aims to tackle the problem of reluctance to give alms using Joseph Harrod's contextual theological perspective, namely the discipline of giving alms proactively, as a solution in responding to the socio-economic disparities experienced by society, especially within the Church. This study uses qualitative methods through text analysis and data collection through literature studies. The results of the study found that the concept of the discipline of proactive giving can bridge the socio-economic gap and renew the spiritual life of Christians.